Technology Neutrality as a Way to Future-Proof Regulation: The Case of the Artificial Intelligence Act - Ojanen, Atte (Cambridge University Press, 2026)
Technology neutrality is a guiding principle of the European Union’s technology regulation, stating that legislation should not favour or discriminate against any particular technology, but rather focus on the effects or functions of technologies broadly. This article examines the principle as a way to future-proof regulation by allowing legislation to adapt to the changes in technology over time. Effects of technology neutrality have not been sufficiently analysed in the novel context of regulation of artificial intelligence, which arguably poses more significant societal risks than telecommunications, where the principle first evolved. To address this gap in research, this article analyses whether the technology neutral nature of the EU’s Artificial Intelligence Act (AI Act) renders it more future-proof. It identifies three main factors that affect future-proofness of the AI Act in light of technology neutrality: definition of AI, the risk-based approach and its enforcement mechanisms. The findings indicate that the AI Act’s deviations from technology neutrality, including specific provisions for general-purpose AI models significantly improved its scope and future-proofness. Thus, technology neutrality and future-proof regulation should not be treated synonymously, and strict adherence to neutrality may even obscure the political choices and democratic agency essential for AI regulation.